Enhanced NO2 and aerosol extinction observed in the tropospheric column behind lake-breeze fronts using MAX-DOAS. (January 2020) - Davis, Zoe .Y.W.; Sills, David M.L.; McLaren, Robert
Abstract: The lake breezes that frequently occur in Southern Ontario impact the levels of pollutants experienced by the populations in urban areas. The effects of lake breeze circulations on pollution transport and processing are not well understood. Few studies have measured the circulations' impact on pollutants both at the surface and within the tropospheric column. In this study, pollutants in the tropospheric column (NO2 VCDs and AODs) were measured using MAX-DOAS concurrent with near-surface measurements of NOx, O3, and PM2.5 on lake breeze days in Toronto in September and October. The arrival of lake-breeze fronts (LBF) was identified using co-located meteorological data. The presence of lake breezes was confirmed using mesoscale analyses of radar, satellite and a network of meteorological stations. NO2 VCDs exhibited short-term increases of 0.8-3.4×10 16 molecules cm -2 above the pre-LBF levels following the arrival of a LBF. These measurements are the first confirmation of the theorized presence of enhanced total burden of pollution within the total column behind the front within a lake-breeze circulation on multiple lake breeze days. Rapid decreases of O3 of up to 13 ppb at the arrival of the LBF were unexpected based on observed increases in O3 in other studies, but can be attributed to reduced photochemical O3 production during late summer and fall compared to mid-summer. AODs exhibited delayed enhancements compared to NO2 VCDs, appearing to be driven by enhanced humidity following the front, in addition to enhanced particle concentration. Our measurements highlight the complex 3-D structure of lake-breeze circulations. Highlights: Impact of lake breeze on NO2 VCDs and AODs is investigated in Toronto by MAX-DOAS. NO2 VCDs briefly increased 0.8-3.4×1016 molecules cm-2 following arrival of a LBF. Near-surface O3 decreased up to 13 ppb at the arrival of the lake-breeze front. AODs exhibited delayed enhancements compared to NO2 VCDs. Total burden of pollution was enhanced within the total column behind the front.